2019
DOI: 10.1016/j.jpainsymman.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on Quality of Life, Fatigue, Physical Function, and Safety in Advanced Solid Tumor Cancers: A Meta-analysis of Randomized Control Trials

Abstract: Background. People with metastatic cancers experience poor quality of life (QoL), fatigue, and decreased physical function. Exercise improves these symptoms in the curative setting, but the efficacy and safety of exercise in the metastatic setting is uncertain.Methods. Prospective, randomized trials of moderate/high-intensity aerobic exercise or resistance training vs. control in patients with advanced/metastatic solid cancers were identified from prior reviews and updated using a search of PubMed. The mean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 64 publications
2
38
0
3
Order By: Relevance
“…As noted in the introduction, findings from several systematic reviews and metaanalyses, [26][27][28][29][30][31][32][33][34] suggest that multimodal exercise interventions are effective in decreasing fatigue. This study is the first to evaluate the relationships between levels of exercise and selfreports of morning and evening fatigue, as well as decrements in morning and evening energy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As noted in the introduction, findings from several systematic reviews and metaanalyses, [26][27][28][29][30][31][32][33][34] suggest that multimodal exercise interventions are effective in decreasing fatigue. This study is the first to evaluate the relationships between levels of exercise and selfreports of morning and evening fatigue, as well as decrements in morning and evening energy.…”
Section: Discussionmentioning
confidence: 95%
“…[23] Given that an alteration in inflammatory responses associated with the administration of CTX is one of the hypothesized mechanisms for both fatigue and sleep disturbance, a number of randomized clinical trials have evaluated the efficacy of exercise for these symptoms. In terms of fatigue, across several systematic reviews and meta-analyses of patients undergoing active treatment as well as cancer survivors, [26][27][28][29][30][31][32][33][34] the findings suggest that multimodal exercise interventions that include aerobic, resistance, and stretching exercises are effective in decreasing fatigue. While less well studied and often evaluated as a secondary outcome, [35][36][37][38] findings from four systematic reviews suggest that regular exercise results in decreases in sleep disturbance.…”
Section: Introductionmentioning
confidence: 98%
“…A substantial proportion of these patients suffer from typical adverse effects of the disease itself and its treatments (e.g., fatigue, deconditioning), causing disruption in all aspects of quality of life (QoL). Regular strength and endurance training potentially mitigates tumor-and treatment-related adverse effects and consequently have beneficial effects on QoL, physical fitness, and cancer-related fatigue [3][4][5]. Furthermore, exercise has been demonstrated to reduce all-cause, cancer-related, and cardiovascular disease mortality [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models, as well as clinical studies on elite athletes and healthy subjects, indicate the positive effect of physical activity on gut microbiota diversity and the production of beneficial metabolites [ 206 , 207 ]. Importantly, several clinical trials concerning cancer survivors have reported an association between exercise and clinically meaningful improvements in quality of life [ 208 ] and mortality [ 209 ]. However, the relationship between exercise and gut microbiota in cancer survivors requires further investigation.…”
Section: Gut Microbiota Modulation As An Emerging Trend In Cancer mentioning
confidence: 99%